2021
DOI: 10.3390/polym13060965
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Optimization of Polymer Powder Plasma Treatment for Composite Materials

Abstract: This paper describes a newly developed testing method for determination of the adhesivity of a film sintered from thermoplastic powder. This method is based on the modified EN 15337 standard. Application of this method enables an effective development of thermoplastic composites with enhanced adhesion between reinforcement and matrix and/or high-quality joints between plastics and dissimilar materials. The proposed method was successfully tested on a series of polyethylene powders treated in the oxygen atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The images show that there are no gaps between the fibers and PE matrix, and there is an increase in the amount of polyethylene residue left on the fiber surface after breaking; this indicates good adhesion between the fiber and the matrix. These images are consistent with those of Zuzana et al [42]. on the adhesion between treated material and glass rods.…”
Section: Morphologysupporting
confidence: 92%
See 2 more Smart Citations
“…The images show that there are no gaps between the fibers and PE matrix, and there is an increase in the amount of polyethylene residue left on the fiber surface after breaking; this indicates good adhesion between the fiber and the matrix. These images are consistent with those of Zuzana et al [42]. on the adhesion between treated material and glass rods.…”
Section: Morphologysupporting
confidence: 92%
“…This indicates that a longer heating time is needed to prepare composites using powder treated for a longer time. These results correspond with the results obtained by Z. Weberova et al, on the sintering of plasma-treated polyethylene on glass rods in an oven which showed that plasma treatment time of the polyethylene powder affected their sintering behavior and longer time is needed to obtain a proper sintering of the powder [42]. The tensile strength of the composites prepared using treated and untreat fibers is presented in Figure 12.…”
Section: Effect Of Oven Temperature and Holding Timesupporting
confidence: 89%
See 1 more Smart Citation
“…Adhesion was characterized by shear strength, measured using a modified pin-collar test, a method adapted for the measurement of the adhesion of polymer powders to solid substrates. The same procedure as that described by Weberova et al [22] was used. Rods made from chrome-plated steel C35 with a fine smooth surface (Ra max = 0.2 µm, average Ra = 0.13 µm) with d = 12 mm, l = 45 mm (Hydraulics s.r.o., Slopné, Czech Republic), were used as a metal substrate.…”
Section: Methodsmentioning
confidence: 99%
“…This method is an eco-friendly approach creating a wide range of reactive species in the polymers, such as amine, hydroxyl, carboxyl, ether, peroxide and carbonyl groups, depending on the surrounding medium. Plasma treatment enhances the surface roughness and hardness properties of the composites [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%